Complications of Nd Yag Laser Capsulotomy - Abdul Matin, Md; Shaheen, Mahbubur Rahman; Farhana, Zakia; Abdul Khaleque, Sajed (Medicine Today, 2023)
Introduction: Aim and objective is to study the intra and post laser complications of Nd yag laser posterior capsulotomy and to find out the incidence of complications. Materials and Methods: This study was conducted in the department of ophthalmology, Ad-Din Women Medical College 2, Bara moghbazar, Dhaka from July 2018 to June 2022. Our study included 206 patients of 220 eyes with significant PCO. Before laser capsulotomy all patients were assess by routine slit lamp examination, IOP measurement and posterior segment examination done for every patient for exclusion of gross posterior segment pathology. Nd yag laser capsulotomy was carried out under topical anesthesia. These patients were assessed for post laser visual acuity and complications in 1st POD after 7 day and 1 month. Every patients with post laser routine medications and as per need of other related eye problems. Result: Total 220 eyes of 208 patients included in our study ,including 93 male (44.71%) and 115 female (55.29%).Range of age were 21yrs to 87 years. Laser capsulotomy were done one eye in 208 patients and both eyes in 14 patients. Range of energy used in our study from 1 to 4.5 mJ. Complications were noted after yag laser capsulotomy In 29 eyes (13.76%) though after taking maximum precaution for avoiding complications including pre laser slit lamp examination, assessment of IOP, proper dilatation of pupil, power setting were minimum as per as possible. Conclusion: The Nd yag laser capsulotomy is an effective, safe procedure for the treatment of opaque posterior capsule which is unique and magical approach for improvement of vision and restoration of effective life style. Every procedure have some adverse effect, Nd yag laser capsulotomy also have some complications .but benefit are tremendous if we can go in proper way. Medicine Today 2023 Vol.35(2): 91-94